Developing Children's Social Empathy as a Means of Preventing Bullying - Ulfa Ainul Mardhiyah; Avita Febri Hidayana (Child Kingdom : Jurnal Pendidikan Anak Usia Dini, 2024)
Empathy is one of the risk factors and solutions to bullying behavior, This can be an alternative for some parties in handling bullying cases, namely by fostering social empathy by parents, communities and schools. Social empathy must be introduced and trained from early childhood including elementary school age, Considering that bullying cases occur quite a lot in the environment of elementary school-age students. This study aims to identify bullying behavior among Madrasah Ibtidaiyah students, Dealing comprehensively with the cultivation of social empathy attitudes and to know the role of family and environment in influencing the development of empathy. The strategy we use in this study is to first find the problems that exist in the institution, Then we study to be able to get solutions to existing problems. In finding and reviewing existing problems, we use qualitative descriptive methods. Based on the results of the study, there are still children who have low empathy. This happens partly because; the presence of errors in the parenting process, the influence of the community environment and peers, and because children have experienced physical and psychological violence. Therefore, from the school side, there needs to be steps that are able to increase children's social empathy